Review paperThe role of flavonoids in asthma - Pałgan, Krzysztof; Bartuzi, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Dietary change is considered to be one of the environmental factors that cause allergic diseases such as asthma, atopic dermatitis and allergic rhinitis. Epidemiological and animal asthma model studies have suggested that flavonoids may protect against asthma. These compounds have profound effects on the function of immune and inflammatory cells, as confirmed in a large variety of in vitro and in vivo studies. Flavonoids, ubiquitously present in fruits, vegetables, teas and wine, possess anti-allergic properties and ameliorate asthma symptoms.